ANALISIS ETIKA BISNIS ISLAM TERHADAP PRODUKSI KERUPUK RAJUNGAN DI DESA POLAGAN - SEIDI, NAQSYABAN SEIDI AKBAR (Qawwam : The Leader's Writing, 2021)
This study aims to determine how the concept and application of Islamic business ethics in the production process of crab crackers in Polagan Village, Galis District, Pamekasan Regency. The purpose of this study is to understand what the concept of Islamic business ethics is and how it is applied in the production process, so that the results of this research resume can be used as a framework or model for other businesses in the future. The research method used in this study is qualitative with the type of field research, and data collection techniques are interview, observation and documentation techniques. This research is analytical descriptive. The data obtained from the field will be collected and analyzed using the point of view of Islamic business ethics which is presented in the form of a description with inductive thinking, namely a collection of facts that occur in the field in the analysis and then draw conclusions. The results show that the crab cracker production process in Polagan village has implemented and implemented the principles of Islamic business ethics. In carrying out their business and activities, business actors understand and apply Islamic principles or values ​​in the following ways: Based on the Qur'an and As-Sunnah.